Clinical assessment of a circadian‐based antioxidant system combined with a comprehensive brightening serum in diverse subjects with moderate‐to‐severe facial hyperpigmentation. (21st March 2022) - Shah, Sachit; Manry, Shelly; Makino, Elizabeth T.; Mehta, Rahul C.
Abstract: Background: Hyperpigmentation conditions can affect all skin types but occur more frequently in darker skin. Because many factors have been implicated in the etiologies of these disorders, multi‐targeted approaches may be required to achieve a better overall outcome in a diverse patient population. Aims: The purpose of this study was to investigate the safety and efficacy of a combination regimen of a comprehensive cosmetic brightening agent (LYT2) with a broad blend of antioxidants (LVS) to reduce hyperpigmentation and improve overall skin appearance. Methods: The combination of LYT2 and LVS, in addition to a basic skincare routine, was evaluated in subjects of either Caucasian or Asian (a majority of whom were Indian) descent, presenting with moderate‐to‐severe hyperpigmentation. Efficacy evaluations consisted of investigator clinical grading of overall hyperpigmentation, skin tone evenness, and radiance, as well as subject self‐assessment questionnaires. Results: Immediate and progressive improvement was noted by the investigators for all assessed parameters. At the end of the 12‐week study, investigators observed a 45% mean decrease from baseline for overall hyperpigmentation. In addition, a 50% improvement in skin tone evenness and a 58% increase in radiance was observed. These investigator assessments were matched by good patient scores for self‐perceived efficacy parameters and high overall satisfaction. One patient (7%) showed a treatment‐related adverse event. Conclusion: A combination skincare regimen that combines the pigmentation control of LYT2 with the broad antioxidant defense of LVS is a well‐tolerated and effective treatment option to improve the appearance of facial hyperpigmentation and make skin more radiant.